2022
DOI: 10.1038/s41467-022-31400-6
|View full text |Cite
|
Sign up to set email alerts
|

Chain flexibility of medicinal lipids determines their selective partitioning into lipid droplets

Abstract: In guiding lipid droplets (LDs) to serve as storage vessels that insulate high-value lipophilic compounds in cells, we demonstrate that chain flexibility of lipids determines their selective migration in intracellular LDs. Focusing on commercially important medicinal lipids with biogenetic similarity but structural dissimilarity, we computationally and experimentally validate that LD remodeling should be differentiated between overproduction of structurally flexible squalene and that of rigid zeaxanthin and β-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…As an intracellular product, the maximal amount of squalene is limited by the available biomass. In addition, the accumulation of lipids is beneficial for squalene production due to their role as a storage compartment for this hydrophobic product (Son et al, 2022). However, lipid production competes with squalene for the common precursor acetyl‐CoA (Liu et al, 2020), resulting in the need for a fine‐tuned balance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As an intracellular product, the maximal amount of squalene is limited by the available biomass. In addition, the accumulation of lipids is beneficial for squalene production due to their role as a storage compartment for this hydrophobic product (Son et al, 2022). However, lipid production competes with squalene for the common precursor acetyl‐CoA (Liu et al, 2020), resulting in the need for a fine‐tuned balance.…”
Section: Resultsmentioning
confidence: 99%
“…As an intracellular product, the maximal amount of squalene is limited by the available biomass. In addition, the accumulation of lipids is beneficial for squalene production due to their role as a storage compartment for this hydrophobic product (Son et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…General experimental information, methods, Figures S1−S14, Tables S1 and S2, and 1 H, 13 C, and HRMS spectra for LD-CF (PDF)…”
Section: ■ Associated Contentmentioning
confidence: 99%
“…Ma et al (2019) observed lycopene accumulated in LDs of S. cerevisiae. The hydrophobic compounds are distributed in different parts of LDs due to their different structures (Son et al, 2022b). Adjusting organelle morphology can be a useful strategy for increasing terpenoid production, which will be introduced in detail below.…”
Section: Providing a Suitable Environment For The Production Of Trite...mentioning
confidence: 99%
“…Son et al reported that flexible lipids such as squalene with conjugated π bonds are readily dispersed among TAGs, and squalene production can be enhanced by expanding the volume of the LD. Similarly, rigid lipids such as zeaxanthin and β-carotene are retained between TAGs, and the production of zeaxanthin was enhanced by increasing the LD surface area within the cell (Son et al, 2022b). Thus, LDs are suitable organelles for storing triterpenoids and tetraterpenoids, while strategies that control the size and the number of organelles influence their storage capacity (Figure 4).…”
Section: Lipid Dropletsmentioning
confidence: 99%